2012
DOI: 10.1061/(asce)be.1943-5592.0000228
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation, Nondestructive Testing, and Finite-Element Model Updating for Bridge Evaluation Using Strain Measurements

Abstract: A baseline finite element model was developed for bridge management and calibration using nondestructive test data. The model calibration technique was evaluated on the Vernon Avenue Bridge over the Ware River in Barre, Massachusetts. This newly constructed bridge was instrumented throughout its construction phases in preparation for a static truck load test performed before the bridge opening. The strain data collected during the load test was used to calibrate a detailed baseline finite element model in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 16 publications
0
80
0
Order By: Relevance
“…Sanayei et al (2011) presented a manual model updating example where model predictions are manually compared to measurements and the model is calibrated based on engineering knowledge to minimize an objective function. A typical objective function for residual minimization is shown in equation (1):…”
Section: Residual Minimizationmentioning
confidence: 99%
“…Sanayei et al (2011) presented a manual model updating example where model predictions are manually compared to measurements and the model is calibrated based on engineering knowledge to minimize an objective function. A typical objective function for residual minimization is shown in equation (1):…”
Section: Residual Minimizationmentioning
confidence: 99%
“…In long bridges with connectivity importance as Chacao Channel Bridge, the investment in instrumentation represents a small amount of the total project cost. Moreover, it is important to have continuous monitoring in order to update the properties of the bridges over time, as proposed by Sanayei (Sanayei et al, 2012). In this way it is possible to detect changes in the structures that may indicate weakening due to earthquakes, accidents, damage caused by the action of environment or other, and take actions to repair or reinforce them.…”
Section: Discussionmentioning
confidence: 99%
“…Ahlborn et al [76] applied different image technologies in assessing the condition of concrete bridge decks and reported that the 3DOB or BVCR techniques based on close range 3D photogrammetry and the GigaPan technique based on street view-style photography are the best technologies for defect measurement for bridge inspections. The DIC technology uses mathematical algorithms to extract displacement information from a series of photographs and can be used to calculate load rating of BCA throughout the service life of the bridge [77]. Hinzen [78] demonstrated the feasibility of damage detection and quantification based on google street view images.…”
Section: Nde Using Remote Sensing Technologiesmentioning
confidence: 99%